D-Whiz in ICT skills development : exploratory : programming, web design, database, troubleshooting - Innovative Training Works (Sampaloc Manila : Rex Book Store, Inc., 2018)
"The Digital Whizkids Computer Literacy Program is the result of almost 20 years of experience, research, and development on the educational needs of the K to 12 student population. The Digital Whizkids - 21st Century Learning ProSkills Series is a complete series that was designed and developed to equip students with the computer skills and knowledge needed to be competent individuals in the information age. It aims to bring quality computer education that adopts the DepEd curriculum for information and Communication Technology (ICT) and is completely aligned with global competency certification objectives which conform to the 21st century learning design. It is the most effective way to teach students real-world computing skills which will last a lifetime and lay the foundation for higher education."
Includes bibliography and index.
English text.
Keywords: Computer software